Management of financial institutions and risks under uncertainty - Bardas, Artem; Dudnyk, Alla; Avramenko, Oleksandr; Kazymyrenko, Oleksii (Management and Entrepreneurship: Trends of Development, 2022)
The purpose of this study is to examine the purpose of this study is to examine the features of managing financial institutions and risks under conditions of uncertainty. The current period of development of the financial sphere is characterized by availability of a significant number of approaches and methods of management through forecasting and assessing risks, their identifying and minimizing. Analysis of recent research and publications has shown that the use of innovative mathematical management methods can minimize risks and provide significant competitive advantages in the future. Methodology: general and special methods of system-structural analysis and synthesis, grouping and comparison were used in the research process. The risk management scheme proposed by the NBU for use by financial institutions has been analyzed and supplemented by taking into account reputational risks. The research findings show that the existing methods are based on the use of expert judgment and require a significant amount of information that is not always available. It has been proven that the construction, use, calibration and interpretation of results obtained during risk assessment should be handled by a risk committee, whose main task is to monitor, identify and manage risks that arise during the operation of the financial institution. It has been revealed that there is no single complete Bureau of Credit Histories in Ukraine, which is a significant barrier to the effective management of financial institutions. The prospect for further research is the formation of approaches that would allow managing several types of risks, in compliance with all regulations under current legislation. This will make it possible to fully satisfy customers, while the setup of a single bureau of credit histories will minimize risk manifestations.JEL Classification: G18, G20, D81